“Saw you in the dark”: Exploring Rufus Wainwright’s emotional vulnerability in fan-captured live performance videos - Salerno, Stephanie (Performance Matters, 2019)
A Victorian-inspired, deplumed, black mourning gown; a video of a kohl-painted eye, staring, blinking, and weeping; and a baritone voice mingling with solo piano are the audio and visual touchstones of Rufus Wainwright’s 2010 live tour of All Days Are Nights: Songs for Lulu. Using performance analysis of fan-captured performances posted on YouTube, this article argues that digital viewership queers, or alters, the audience’s experience, thus empowering spectators to engage with the emotional vulnerability, grief, and genre-bending of Lulu. For a work like Lulu, performed as a song cycle and without official music videos or a professional live recording, fan videos fill a void, at once cutting a major expense of the artist/label while empowering the audience to capture and share what they find to be meaningful online. In this study, four fan-captured live Lulu performances reveal moments of elision, uncertainty, and the blurring of the artist and the artist’s persona within digital “third space.” Through this lens, persona and grief are read within digital viewings of Wainwright’s live performances while framing online spectatorship as a queer practice of meaning-making.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amériques; approches et analyses; culture populaire; deuil; identités LGBTQIA2+; masculinité; médias sociaux; new york; périodes historiques; queer; représentations médiatiques; ressource en ligne; régions géographiques; sofia; stéréotypes de genre; thématiques

True loves, dark nights: Queer performativity and grieving through music in the work of Rufus Wainwright - Salerno, Stephanie (Université d'État de Bowling Green, 2016)
This dissertation studies the cultural significance of Canadian-American singer/songwriter Rufus Wainwright's (b. 1973) album All Days Are Nights: Songs for Lulu (Decca, 2010). Lulu was written, recorded, and toured in the years surrounding the illness and eventual death of his mother, beloved Quebecoise singer/songwriter Kate McGarrigle. The album, performed as a classical song cycle, stands out amongst Wainwright's musical catalogue as a hybrid composition that mixes classical and popular musical forms and styles. More than merely a collection of songs about death, loss, and personal suffering, Lulu is a vehicle that enabled him to grieve through music. I argue that Wainwright's performativity, as well as the music itself, can be understood as queer, or as that which transgresses traditional or expected boundaries. In this sense, Wainwright's artistic identity and musical trajectory resemble a rhizome, extending in multiple directions and continually expanding to create new paths and outcomes. Instances of queerness reveal themselves in the genre hybridity of the Lulu song cycle, the emotional vulnerability of Wainwright's vocal performance, the deconstruction of gender norms in live performance, and the circulation of affect within the performance space. In this study, I examine the song cycle form, Wainwright's musical score and vocal performance, live performance videos, and fan reactions to live performances in order to identify meaningful moments where Wainwright's musical and performative decisions queer audience expectations. While these musical moments contribute to the already rich and varied lineage of the gay male artist in both classical and popular music, I argue that Wainwright's queer performativity and nontraditional musical choices speak to larger issues important to American culture in the contemporary moment. These issues include the visibility of male public mourning and the healing power of artistic expression in the face of traumatic loss.
https://scholarworks.bgsu.edu/acs_diss/90
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; culture populaire; deuil; discipline; genre; mémoires/thèses; philosophie; périodes historiques; queer; ressource en ligne; résistance; sciences humaines; émotions